Legal Analysis of Compensation for Building Failure - Endry Zhulham Pratama; Sami'an Sami'an; Sarwono Hardjomuljadi; Dwi Edi Wibowo (Interdisciplinary Social Studies, 2025)
Building failure is a multidimensional problem in the construction sector that includes aspects of agreements, technical performance, and civil consequences. This study examines legal arrangements related to building failures in Indonesia, reads the pattern of accountability in a number of Supreme Court decisions, and contrasts it with international practice. The research was conducted through the search for regulations, court decisions, and academic literature as the basis for normative analysis. The findings show that the absence of uniform technical investigation procedures, weak project documentation, and differences in expert approaches also trigger differences in verdicts. As a new contribution, this study introduces the Building Failure Integrated Analysis Model (MAT-KB) which combines contract analysis, tort principles, forensic evaluation, and economic considerations to strengthen the accuracy and consistency of dispute resolution. This model is considered to be able to provide a more comprehensive evaluation framework for construction law practice in Indonesia.